2017
DOI: 10.1002/mrm.26904
|View full text |Cite
|
Sign up to set email alerts
|

Joint arterial input function and tracer kinetic parameter estimation from undersampled dynamic contrast‐enhanced MRI using a model consistency constraint

Abstract: The proposed model-based DCE-MRI reconstruction enables the use of different TK solvers with a model consistency constraint and enables joint estimation of patient-specific AIF. TK maps and patient-specific AIF with high fidelity can be reconstructed at up to 100-fold undersampling in k,t-space. Magn Reson Med 79:2804-2815, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The readout dimension was fully sampled while the phase encode dimensions were acquired along rasterized spiral-in trajectories. The B 1 + maps were estimated by techniques (9)(10)(11)(12), a similar characterization has not yet been performed for high-spatiotemporal-resolution whole-brain DCE MRI systems with sparse sampling. Characterization of measurement uncertainty relies on reproducibility studies in controlled test-retest settings.…”
Section: Sparse Dce Mri Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The readout dimension was fully sampled while the phase encode dimensions were acquired along rasterized spiral-in trajectories. The B 1 + maps were estimated by techniques (9)(10)(11)(12), a similar characterization has not yet been performed for high-spatiotemporal-resolution whole-brain DCE MRI systems with sparse sampling. Characterization of measurement uncertainty relies on reproducibility studies in controlled test-retest settings.…”
Section: Sparse Dce Mri Data Acquisitionmentioning
confidence: 99%
“…Sparse DCE-MRI Reconstruction MethodsLebel et al (10) demonstrated reconstruction of high-spatial-resolution whole-brain DCE MRI time series from highly undersampled raw k-space data for tracer-kinetic parameter estimation. Guo et al(12) demonstrated joint estimation of tracer-kinetic parameter maps and patientspecific VIF. In the current study, we extended the sparse SENSE (SPSENSE) framework by Lebel et al(10) and the model consistency constrained (MOCCO) method by Guo et al(12) with an automated delineation of brain vessels based on common image/time series features in the literature…”
mentioning
confidence: 99%
“…The optimization process is as given below: Eqs. (20) and (21), where Eq. (21) was solved using conjugate gradient (CG) and Eq.…”
Section: D Modlmentioning
confidence: 99%
“…Contrary to the indirect methods, Guo et al 19,20 and Dikaois et al 21 estimated the TK parameters directly from undersampled k-t space data without going into image domain. Their experiments have shown that direct reconstruction methods, perform better than the indirect methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation